Microsatellite loci-based genetic relatedness holds key to parental selection for Sesame (Sesamum indicum L.) improvement: Microsatellite loci-based genetic relatedness holds key to parental selection for Sesame (Sesamum indicum L.) improvement - K MUKHTHAMBICA; H H KUMARASWAMY; K T RAMYA; R BISEN (Journal of Oilseeds Research, 2023)
Microsatellite-based DNA-level diversity and genetic relatedness assessments empower parental selection in sesame crop improvement. A panel of 70 sesame varieties that were analyzed for 40 microsatellite loci got grouped into 5 distinct cluster based on Jaccard’s coefficient at genetic distance of 0.2. Nei coefficient analysis deciphered the presence of the maximum genetic distance between cluster 1 and cluster 5. The members of cluster 1 can be crossed with that of cluster 5 to get better allelic combinations. The findings of the present help selecting parental lines from a panel of 70 varieties for sesame crop improvement program.